Emerging gene editing strategies for Duchenne muscular dystrophy targeting stem cells - Bertoni, Carmen (Frontiers in Physiology, 2014)
The progressive loss of muscle mass characteristic of many muscular dystrophies impairs the efficacy of most of the gene and molecular therapies currently being pursued for the treatment of those disorders. It is becoming increasingly evident that a therapeutic application, to be effective, needs to target not only mature myofibers, but also muscle progenitors cells or muscle stem cells able to form new muscle tissue and to restore myofibers lost as the result of the diseases or during normal homeostasis so as to guarantee effective and lost lasting effects. Correction of the genetic defect using oligodeoxynucleotides (ODNs) or engineered nucleases holds great potential for the treatment of many of the musculoskeletal disorders. The encouraging results obtained by studying in vitro systems and model organisms have set the groundwork for what is likely to become an emerging field in the area of molecular and regenerative medicine. Furthermore, the ability to isolate and expand from patients various types of muscle progenitor cells capable of committing to the myogenic lineage provides the opportunity to establish cell lines that can be used for transplantation following ex vivo manipulation and expansion. The purpose of this article is to provide a perspective on approaches aimed at correcting the genetic defect using gene editing strategies and currently under development for the treatment of Duchenne muscular dystrophy (DMD), the most sever of the neuromuscular disorders. Emphasis will be placed on describing the potential of using the patient own stem cell as source of transplantation and the challenges that gene editing technologies face in the field of regenerative biology.